Selected ore deposits of Brazil - HAGEMANN, Steffen (2008)
This series of papers on a variety of ore deposits in Brazil is the outgrowth of the “First Brazilian Symposium on Metallogeny” held in Gramado, Rio Grande do Sul, in May 2005. The selection of papers mirrors quite well the range of commodities and fascinating diversity of ore deposit types Brazil has to offer. The thematic issue starts with a paper by Monteiro et al who use detailed petrography to establish a consistent paragenetic sequence of alteration and mineralization throughout the Sossego iron–oxide–copper–gold (IOCG) deposits in the giant Carajás Mineral Province. Combined with stable isotope data, it allows the authors to constrain the|spatial and temporal zoning of hydrothermal alteration and mineralization. They conclude that the Pista-Sequerinho-Baiano and Sossego-Curral ore bodies formed at a deep and high structural level of an IOCG system, respectively. Significantly, the copper–gold mineralization was late in the alteration history and broadly synchronous in both ore bodies